Frontend Web Development Bootcamp - Build a Twitter Clone - Lomidze, George (Packt Publishing, 2020)
Master frontend web development using HTML, CSS, CSS Flexbox, CSS Grid, and JavaScript About This Video Learn HTML, CSS, JavaScript, and DOM in a single course Explore basic to advanced fundamental concepts of frontend web development Build a fully responsive web app that works across different screen devices In Detail If you want to learn how the most popular and widely used websites are created, this Frontend Web Development Bootcamp is for you. In this course, you'll build a website by cloning Twitter. Before you start building the website, you'll be taken through each of the technologies that you need to be well-versed with to build this project. Starting with HTML and CSS, you'll build three different pages for your app - the main page, login page, and newsfeed page. Once you've got to grips with JavaScript and DOM, you'll add some functionality to your project. With the step-by-step instructions, this course will guide you in creating some validation to navigate between different pages. You'll also be able to build different modal boxes, create a sidebar, and add a dark mode. Finally, you'll make your project fully responsive on different screen sizes, so it's compatible with all types of devices. By the end of the course, you'll have learned the skills necessary to master Responsive Web Design.